(untitled) (International Journal of Multidisciplinary Research and Explorer, 2020)
Due to the outbreak of COVID-19, people’s working lifestyles around the world are affected by lockdown and working from home. Most of the public and private sectors then need to deal with this crisis which causes impacts on humans in various dimensions and brings about new behaviors in a human society. Therefore, this academic article aims to study a new normal of strategic management by using a literature review from various sources such as academic articles, interviews and other relevant information, and then summarizing and synthesizing them into work management strategies, people management strategies as a guideline in management planning for both the public and private sectors’ strategic management in the future.